Influence of composition of soilless substrates monitored with iot sensor nodes on the growth, nutrient and fruit quality of rockmelons (Cucumis melo Var. Cantalupensis) - Ridzwan Che Rus (Tanjung Malim, 2023)
Influence of composition of soilless substrates monitored with iot sensor nodes on the growth, nutrient and fruit quality of rockmelons (Cucumis melo Var. Cantalupensis) by Ridzwan Che Rus